THE EFFECT OF PLANT NUTRITION ON THE AGROPHYSICAL PROPERTIES OF DARK LIGHT GREY SOILS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
In this article, it was studied that root fertilization and fertilization through the leaves of plants developing in the spring period allowed to improve the agrophysical properties of soils. It was found that as a result of leaf fertilization of plants developing in spring (HUMIMAX,0.5 l/ha) and root fertilization (NH4NO3, 50 kg/ha), the volume weight decreased by 0.03-0.04 g/sm3, soil porosity increased by 2.2-1.6 %